Replacement of chloroform in total egg lipid extraction - Gayapa, Purple G. (2016.)
Lipids are an important source of energy and essential in maintaining bodily functions. The lipid extraction plays an important role in subsequent analysis such as fat content determination. The lipid extraction method being used in the University laboratory is the modified Folch method which employs the use of toxic solvents such as chloroform:methanol solvent system to minimize the chloroform consumption in the modified Folch lipid extraction and to optimize the replacement solvent system for maximum lipid yield. The sample was extracted using various alternative solvent systems with the ratio of 2:1 (v/v). The highest lipid yield was obtained from the 2:1 cyclohexane:isopropanol solvent system with actual yield equal to 0.029 ± 0.010g actual yield and percent yield of 0.57 ± 0.20% which is significantly higher than the yield from chloroform:methanol solvent system (actual yield equal to 0.0054 ± 0.0004g and percent yield of 0.108 ±0.007%).
Thesis -- Bachelor of Science in Chemistry. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Lipids; Lipid extraction; Folch method; Chloroform; Egg yolk